Impact of Covid 19 Pandemic on the performance of Medical Aid Societies In Zimbabwe - Tanaka T. T Mutero; Blessed Mveku; Peter Bhibhi; Munyaradzi Chagwesha; Mike Mudzamba (Macrothink Institute., 2023)
This research study was inspirational to know and understand the impact of COCOVID-19andemic on the performance of Medical Aid Societies in Zimbabwe. The objectives of the study were to determine the impact of COVID-19 on membership uptake, examine the impact of COVID-19 on the profitability of medical aid and assess the impact of COVID-19 on claims management. A literature review provided the foundation and knowledge, understanding and scholarly debates of the impact of COVID-19 medical aid societies. The study adopted the quantitative research methodology and constructed a questionnaire and conducted interviews distributing them to 80 correspondents. Data collected was analysed using IBM SPSS statistics version 20 and the findings of the data were represented on tables. The hypothesis of the study H0 was accepted as COVID19 had an impact on the membership uptake, profitability, and claims of medical AID Schemes in Zimbabwe. The sample size used was 80. Recommendations on how to manage medical aid societies’ performance in a crisis is according to the findings of the study are proposed. The recommendations include engaged membership, blockchain technology, and hybrid billing model. The study proposed that future researchers can compare the use of telehealth services in other countries during pandemics of this nature and its role in Zimbabwean Medical Aid societies for the sustenance of their performance.